1993
DOI: 10.1007/bf00191120
|View full text |Cite
|
Sign up to set email alerts
|

Inner-sphere oxidation of ethylenediaminetetraacetatocobaltate(II) by N-bromosuccinimide

Abstract: The kinetics of oxidation of [CoI~(EDTA)] 2 (EDTA = ethylenediaminetetraacetate) by N-bromosuccinimide (NBS) in aqueous solution obey the equation:where k2 is the rate constant for the electron-transfer process, K 2 the equilibrium constant for the dissociation of [Con(EDTAH)(H20)] -to [CoJ'(EDTA)(OH)] 3-and K 3 the pre-equilibrium formation constant. The activation parameters are reported. It is proposed that electron transfer proceeds via an inner-sphere mechanism with the formation of an intermediate which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…The rate of oxidation increased by increasing the concentration of [NBS], [complex] and is inversely proportional to the hydrogen ion concentration over the range 4.34-5.52. Oxidation of [Co II (EDTA)] (EDTA = ethylenediaminetetraacetate) and [Co II (HEDTA)] (HEDTA = N-2-hydroxyethyl-ethylenediamine N,N 0 ,N 0 -triacetate) by NBS was found to proceed via the initial formation of cobalt(III) products which is consistent with an inner-sphere mechanism [11,12]. The kinetics of oxidation of [Cr(EDTA) (H 2 O)] -by NBS has been also investigated [13].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…The rate of oxidation increased by increasing the concentration of [NBS], [complex] and is inversely proportional to the hydrogen ion concentration over the range 4.34-5.52. Oxidation of [Co II (EDTA)] (EDTA = ethylenediaminetetraacetate) and [Co II (HEDTA)] (HEDTA = N-2-hydroxyethyl-ethylenediamine N,N 0 ,N 0 -triacetate) by NBS was found to proceed via the initial formation of cobalt(III) products which is consistent with an inner-sphere mechanism [11,12]. The kinetics of oxidation of [Cr(EDTA) (H 2 O)] -by NBS has been also investigated [13].…”
Section: Introductionsupporting
confidence: 54%
“…The succinimidyl radical produced will prefer to abstract hydrogen atom from the solvent to form succinimide rather than dimerize to bisuccinimide [7,8]. N-bromosuccinimide has been used as an oxidizing agent for some transition metal complexes [9][10][11][12][13][14][15]. The kinetics of oxidation of (aqua-2-aminomethylpyridine) Cr III complex by N-bromosuccinimide [9] in aqueous solutions to yield chromium (VI) has been studied spectrophotometrically.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics and mechanism of oxidation of [Co II -(EDTA)(H 2 O)] -2 by NBS have been reported previously [5]. The authors reported that the reaction did not fit either first-or second-order kinetics.…”
Section: Introductionmentioning
confidence: 84%
“…2 ] -(NTA = nitrilotriacetate) by NBS have been studied in aqueous medium [5][6][7]. These reactions were found to proceed via the formation of an initial cobalt(III) product, which converted slowly to the final cobalt(III) product.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation